RABA (Rifka's Applied Behaviour Analysis) Model To Improve Tooth Brushing Skills of Autistic Children - Annisa, Rifka; Djamil, Masrifan; Suwondo, Ari (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Autistic children experience barriers to social interaction, communication, behavior, language, emotion and imagination. Autistic children have different characteristics from children in general. Children are not yet able to brush their teeth properly and there is no special dental health program for children with autism. The RABA (Rifka's Applied Behavior Analysis) is arranged according to their characteristics.This study aimed to develop RABA (Rifka's Applied Behavior Analysis) to improve brushing skills and decrease debris index in children with autistic children.This type of research is uses R&D method and model trial (Quasi-Experiment Pretest and Posttest with Control Group Design). The research subjects of autistic children were divided into 2 groups. The results of the model design are validated by experts. Data were tested using intraclass correlation coefficient, Chi Square, Shapiro wilk, repeated measure annova, independent sample t-test.Expert validation of RABA (Rifka's Applied Behaviour Analysis) model averaged 85.46 (very feasible) to improve brushing skills and decrease debris index of autistic children with a p-valueÂ of 0.000. This model effectively to improve the brushing skills of autistic children with a p-value (0.033) and decrease the debris index of autistic children with p-value (0.004) compared to the control group. The application of the RABA (Rifka's Applied Behavior Analysis) model was effective to improve brushing of autistic children compared to the control group.